Do executive compensation contracts maximize firm value? Indications from a quasi-natural experiment - Abudy, Menachem (Meni); Amiram, Dan; Rozenbaum, Oded; Shust, Efrat (Journal of Banking & Finance, 2020)
We find significant positive abnormal returns surrounding a surprising and quick enactment of a law that restricts executive pay to a binding upper limit in a few industries. We find that the effect is concentrated only for firms in which the restriction is binding. We also find that the increase in value is greater for firms with weaker corporate governance and smaller for firms that grant a greater portion of equity-based compensation to their executives. These results provide indications that, on average, compensation contracts can be set in a way that does not maximize firm value.